Human Resource Management in Muhammadiyah Business Charity: A Case Study of Airmu Ponorogo - Putro, Rizki Listyono; Candrakusuma, Mushlih (Journal of Economics and Management Scienties, 2025)
This research aims to analyze the implementation of human resource management (HRM) in Muhammadiyah Charity, especially in Airmu Ponorogo Charity. The research was conducted using a qualitative method, using in-depth interviews, field observations, and documentation studies to collect relevant data. The results showed that SDI planning at Airmu Ponorogo Charity has been carried out systematically with a focus on meeting the needs of teaching staff and other supporting staff. The recruitment and selection process is conducted transparently, with competence and integrity criteria as the top priorities. In addition, performance management is evaluated through quantitative and qualitative approaches, although there are still challenges regarding the objectivity of the assessment system. The recognition and compensation programs prioritize moral and spiritual incentives, despite financial limitations hindering the provision of more comprehensive rewards. This study identified challenges in developing a data-driven performance evaluation system and attracting highly competent professionals. Consequently, this study suggests that the Airmu Ponorogo Charity Foundation explore collaborative opportunities with other organizations to enhance HRM quality. While HRM at the Airmu Ponorogo Charity Foundation has shown satisfactory performance, but still needs improvement in several aspects to support the achievement of organizational goals.